Pengaruh Kompensasi Finansial dan Non Finansial terhadap Kepuasan Kerja Pegawai (Studi Kasus pada Kecamatan Alang-Alang Lebar Palembang) - Dita Marisa Putri; Dimas Pratama Putra (CV. Doki Course and Training, 2026)
Abstract : The Effect of Financial Compensation and Non-Financial Compensation on Employee Job Satisfaction in Alang-alang Lebar District of Palembang. Without human factors, all company resources cannot be utilized and managed properly. One way to achieve this is the provision of compensation or compensation that can affect employee job satisfaction. The purpose of this study was to determine the effect of financial compensation and non-financial compensation on employee job satisfaction in the Alang-alang Lebar District of Palembang. Data collection was carried out with a questionnaire distributed to 37 permanent employees of Alang-alang Lebar Palembang District. This study uses multiple linear regression analysis and statistical hypothesis testing (F test and t test). The results of multiple linear regression analysis showed the equation of the model Y = 3.501 + 0.580 X1 + 0.314 X2 + e, which means the regression coefficient of financial compensation and non-financial compensation variables is positive, meaning there is a positive relationship between non-financial compensation and job satisfaction. F test results show that there is a significant influence simultaneously financial compensation and non-financial compensation to employee job satisfaction. This was obtained from the Sig. F <Sig α (0,000 <0.05). T test results indicate that partially there is a significant influence of financial compensation on job satisfaction obtained from the Sig. t <Sig α (0,000 <0.05). And partially there is a significant effect of non-financial compensation on job satisfaction obtained from the value of Sig. t <Sig α (0.004 <0.05).